Industrietourismus - Soyez, Dietrich (ERDKUNDE, 1986)
Industries are traditionally considered to have repellent effects on any kind of recreational and touristic activities. This is certainly true where people during their spare time need a compensative environment, distinctly different from their everyday life in heavily urbanized and industrialized regions. This perspective, however, seems to have concealed the obvious: industries themselves have always been centres of attraction for many people interested in technical objects (machinery), industrial architecture, more or less spectacular production techniques (for example in the steel industry) or specific final products. These latter can be of aesthetic interest (e. g. glass), practical usefulness (e. g. shoes) or simply tasty (e.g. beer or nougat...). Hundreds of thousands of visitors in the different branches of industry in every industrialized country testify to the attractiveness of such objects for this specific type of spatial mobility with distinct educational or recreational characteristics. The same is true for the remnants of former industrial activities, be it well preserved industrial monuments or simply ruins of buildings and machinery. Comparable to other well studied forms of spatial mobility, these types of industry-induced activities - for which the term , Industrial Tourism is proposed - are of consider able interest for the geography of Recreation and Tourism. However, they reflect not only various aspects of specific landscape potentials, spatial behaviour and impacts; they may also assume important functions for the economic and psychological revitalization of old industrialized regions in search of a new regional identity.